IoT in Brain-Computer Interfaces for Enabling Communication and Control for the Disabled - Rajarajan, S.; Kowsalya, T.; Gupta, Nukala Sujata; Suresh, P M; Ilampiray, P; Murugan, S. (Communications and Signal Processing, International Conference on, 2024)
The proposed system integrates Internet of Things (IoT) technologies with Brain-computer interfaces to improve disability-related communication and control. BCIs may directly communicate between the brain and external equipment, providing a lifeline for persons with severe physical restrictions. Incorporating IoT concepts may boost BCI efficacy. Integration of BCI with IoT technology demonstrates unique advantages. BCIs may be connected to the IoT framework to provide a more flexible and comprehensive communication and control environment. Thanks to IoT connection, BCIs can seamlessly interface with assistive devices, home automation systems, wearables, and digital platforms. Interconnectedness expands BCIs' reach, improves user experiences, and allows creative applications. It shows how IoT-enabled BCIs may help disabled people connect with their surroundings, enhance their quality of life, and recover independence. The study discusses data security, privacy, latency, and device compatibility difficulties while integrating various technologies. This combination promises immediate practicality and future progress in both sectors, creating a more comprehensive and accessible digital world.